Research and evaluation methods in special education - Mertens, Donna M.; McLaughlin, John A. (Thousand Oaks, California : Corwin Press, 2004)
This excellent resource provides an approach to research and evaluation that helps educators better understand and address the needs of students with various disabilities.
1. Introduction -- 2. Program evaluation -- 3. Literature review -- 4. Quantitative research methods: questions of impact -- 5. Other quantitative approaches: causal comparative, correlational, single-case and survey research -- 6. Qualitative methods -- 7. Mixed methods and mixed model designs -- 8. Identification and selection of research participants -- 9. Information collection -- 10. data analysis, interpretation and use.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION -- RESEARCH -- METHODOLOGY